Post traumatic cerebrospinal fluid rhinorrhea: a descriptive study - Madathumpadikal, Malavika; Dominic, Mathew; Mary, Preethy (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Background: Post-traumatic CSF rhinorrhea occurs following head trauma or after intracranial surgery. Traumatic CSF rhinorrhea can be detrimental with complications such as bacterial meningitis. Methods: Retrospective review of hospital records of post-traumatic patients admitted under neurosurgery department from 2016-2021 was done. 66 patients with CSF rhinorrhea were identified. Their mode of trauma, management and radiological images were reviewed and recorded. Results: Out of the 66 patients, 87.8% were males and average age group 20-30years. 41 resolved with conservative management. Frontal bone was most common site of rhinorrhea. In 61.8% (n=41) patients, fracture was seen in more than one bone/anatomical site. Incidence of post-traumatic CSF rhinorrhea in this study in 6.6%. Conclusions: Early diagnosis and management are important to prevent complications. In majority of cases, the leak subsides with conservative management, hence early surgical intervention is not required.